The efficacy of Zafirlukast as a SARS-CoV-2 helicase inhibitor in adult patients with moderate COVID-19 Pneumonia (pilot randomized clinical trial) - M.Al Ghobain; F. Rebh; A. Saad; A.H. Khan; N. Mehyar; A. Mashhour; I. Islam; Y. Alobaida; A.S. Alaskar; M. Boudjelal; M.Al Jeraisy (Journal of Infection and Public Health, 2022)
Objective: To assess the efficacy of Zafirlukast as a SARS-CoV-2 Helicase Inhibitor in adult patients with moderate COVID-19 symptoms (hospitalized patients with COVID-19 pneumonia who were not admitted to an intensive care unit). Methods: We conducted a randomized, double blind, placebo-controlled, pilot trial with adult patients with moderate COVID-19 pneumonia. The sample was randomized to Zafirlukast 10 mg BD for 10 days plus standard care vs placebo plus standard care. The primary outcome was the complete resolution of all symptoms. The secondary outcomes were the duration of oxygen therapy, and length of hospital stay (LOS). Results: In total, 40 patients were randomized (20 to Zafirlukast and 20 to the control). The time to the resolution of clinical symptoms in both groups was not significantly different. Regarding the fever, 0.3 days [95 % CI, − 1.19, 0.69], p = 0.76, for shortness of breath, the difference was 0.4 days [95 % CI, − 2.67, 3.46], p = 0.68, for cough the difference was 0.2 days [95 % CI, − 1.45, 1.95], p = 0.98, for sputum the difference was 0.5 days [95 % CI, − 0.75, 1.85], p = 0.09, for vomiting the difference was 0.1 days [95 % CI, − 0.50, 0.30], p = 0.93, for fatigue the difference was 0.3 days [95 % CI, − 4.32, 3.62], p = 0.64. The LOS per day for the two groups was not significantly different, 1.1 days [95 % CI,− 2.03, 4.28], p = 0.94, nor was the duration of oxygen therapy per days, 1.3 days [95 % CI, − 1.79, 4.49], p = 0.49. Regarding the 7 category ordinary scale, there was no significant difference between the two groups at day 7 (p-value = 0.62), day 14 (p-value = 0.60) and day 28 (p-value = 0.48). Conclusion: Among adult patients hospitalized with COVID-19 pneumonia, the treatment with Zafirlukast, compared to placebo, did not significantly improve symptoms resolution.